Testing Rigidity Transitions in Glass and Crystal Forming Dense Liquids: Viscoelasticity and Dynamical Gaps - Toledo-Marín, J. Quetzalcóatl; Naumis, Gerardo G. (Frontiers in Materials, 2019)
A computational study of rigidity for dense fluids of monodisperse and bidisperse hard-disks near a phase and a glass transition respectively is presented. To achieve this goal, the transversal part of the dynamical structure factor is calculated. In both cases, a viscoelastic behavior is obtained, with a dynamical gap determined by a critical wavevector kc. Transversal waves exist for k > kc while the maximal correlations happens at frequency ω = 0 for k < kc. In both cases kc goes to zero as the freezing point is approached. Both systems are able to fulfill a scaled dynamical law as a power law is found for the critical kc as a function of the packing. The obtained results indicate that this method gives an alternative to study rigidity and constraint theory in dense fluids, since it is possible to assign a number of floppy modes or broken constraints in the liquid by computing the number of modes below kc, as well as an effective average coordination number. Also, this suggests that the critical wavevector kc can serve as a suitable order parameter.